Harnessing visible light: enhancing TiO2 photocatalysis with photosensitizers for sustainable and efficient environmental solutions - Chauke, Nyiko M.; Mohlala, Reagan L.; Ngqoloda, Siphelo; Raphulu, Mpfunzeni C. (Frontiers in Chemical Engineering, 2024)
The emerging field of using titanium dioxide (TiO2)-based photosensitizers for enhancing photocatalytic removal of thiazine dyes such as methylene blue (MB) from water has long been recognized for its exceptional photocatalytic properties, making it an attractive material for environmental remediation and energy conversion. However, its wide bandgapbandgap limits its responsiveness to visible light. As such, the utilization of TiO2-based photosensitizers for the removal of thiazine dyes, presents a promising avenue for diverse applications. In addressing the dual challenges of environmental pollution and harnessing sustainable energy sources, this review focuses on the removal of thiazine dyes from water and their subsequent application as photosensitizers for TiO2 materials. Thiazine dyes, ubiquitous in industrial effluents, pose environmental concerns due to their persistence and potential toxicity. Conversely, this innovative approach involves employing TiO2 materials as photocatalysts, utilizing the unique properties of thiazine dyes to enhance light absorption. Studies have shown that beyond the conventional role of thiazine dyes as colorants, they can serve as effective photosensitizers when coupled with TiO2. This tandem not only facilitates the elimination of thiazine dyes, such as MB, from water but also augments the improvement of the photocatalytic performance of TiO2 materials. The synergy between dye sensitizers and TiO2 enhances the overall efficiency of processes like dye degradation and water splitting. Dye sensitizers, acting as light energy absorbers, can efficiently transfer this energy to TiO2, thereby promoting electron transfer and generating reactive oxygen species (ROS). These ROS, in turn, initiate chemical reactions, rendering dye sensitizers valuable in applications such as wastewater treatment, solar energy conversion, and environmental remediation. As such, it is crucial to acknowledge the potential drawbacks associated with thiazine dyes, including toxicity and non-biodegradability. Consequently, careful consideration must be given to thiazine dye application and disposal. Therefore, this review manuscript delves into the comprehensive exploration of TiO2-based photosensitizers, shedding light on their efficacy in various photocatalytic processes for thiazine dye removal.